A driving simulator evaluation of potential speed reductions using two innovative designs for signalised urban intersections. (January 2017) - Stephens, Amanda N.; Beanland, Vanessa; Candappa, Nimmi; Mitsopoulos-Rubens, Eve; Corben, Bruce; Lenné, Michael G.
Highlights: Evaluated potential speed reduction of two innovative intersection designs. Designs incorporated aspects of roundabout safety within signalised intersections. Cut-through designed for intersections on dual-carriageway roads with 70+ km/h speed limits. Squircle designed for intersections on single-carriageway roads with 50–60 km/h speed limits. Both designs reduced drivers' speeds approaching and travelling through the intersection. Abstract: Intersections are typically associated with a higher level of crash risk than other types of facilities on the road network. Standard cross-road intersections are particularly hazardous because by their very design, drivers may travel through at speeds that are incompatible with human biomechanical tolerance should a crash occur. Further, drivers are exposed to dangerous conflict angles, which are likely to result in serious injury. This paper examines the effectiveness of two new intersection designs aimed at restricting potentially dangerous conflict angles while reducing driver speeds through the intersection. These designs, named the "Cut-Through" and the "Squircle", incorporate key features of both signalised intersections and roundabouts. The intersections are controlled by signals similar to a signalised roundabout. Instead of a standard central island, right turning traffic (equivalent to left turns in jurisdictions that drive on the right) cut through the central island, thereby avoiding traffic interlocks and delays that can occur with the traditional signalised roundabout. Across two driving simulator studies, vehicle speed data were collected on approach to and through each of the proposed intersection designs. Performance was benchmarked against equivalent standard signalised cross-road intersections and standard non-signalised roundabouts. Notably, drivers reduced their speeds by approximately 30–40% when negotiating both the Cut-Through and the Squircle compared to the standard signalised intersections. The safety potentials of the two new intersection designs are discussed within the guidelines of the Safe Systems principles.